Terminal independent mobility for IP (TIMIP). - Grilo, A. (IEEE Communications magazine)
This article presents Terminal Independent Mobility for IP (TIMIP), which is a new architecture for IP mobility in wireless access networks. TIMIP is based on principles similar to those in the CIP and HAWAII architectures proposed at IETF and is equally suited for micromobility scenarios. With TIMIP, terminals with legacy IP stacks have the same degree of mobility as terminals with mobility-aware IP stacks. Nevertheless, it still uses MIP for macromobility scenarios. In order to support seamless handoff, TIMIP uses context-transfer mechanisms compatible with those currently in discussion at the IETF SeaMoby group